2005
DOI: 10.1097/01.hco.0000166595.44711.6f
|View full text |Cite
|
Sign up to set email alerts
|

An updated clinical primer on large artery mechanics: implications of pulse waveform analysis and arterial tonometry

Abstract: Pulse wave analysis will assist in a better understanding of hypertension as well as in establishing the extent of cardiovascular disease and for monitoring therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
71
0
6

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(79 citation statements)
references
References 67 publications
2
71
0
6
Order By: Relevance
“…Other haemodynamic parameters are associated with stroke in epidemiological studies, 43 and amphetamine appears to alter some of these. Central BP (rather than peripheral brachial BP) is more relevant to the cerebral circulation and amphetamine increased this.…”
Section: Discussionmentioning
confidence: 99%
“…Other haemodynamic parameters are associated with stroke in epidemiological studies, 43 and amphetamine appears to alter some of these. Central BP (rather than peripheral brachial BP) is more relevant to the cerebral circulation and amphetamine increased this.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 The arterial pulse wave is generated by the sum of the forward pressure wave, timing of the reflected wave and the magnitude of the reflected wave along the arterial tree. 18 Arterial wave reflection occurs in the peripheral arteries due to changes in the arterial properties or in the architecture of the arterial tree. 18 Reflected waves can be measured as the augmentation pressure or AI, which has emerged as a surrogate marker for cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…18 Arterial wave reflection occurs in the peripheral arteries due to changes in the arterial properties or in the architecture of the arterial tree. 18 Reflected waves can be measured as the augmentation pressure or AI, which has emerged as a surrogate marker for cardiovascular disease. 11,19 Noninvasive measurement of AI can be performed by direct pulse wave measurement of the common carotid artery or synthesized wave form of the radial artery using the generalized transfer function.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Importantly, the recent Conduit Artery Function Evaluation (CAFÉ ) study showed that a greater decrease of central blood pressure (BP) with antihypertensive treatment is associated with reduced cardiovascular events, independent of peripheral BP changes. 5 Likewise, there are data showing that the reversal of endothelial dysfunction, that is present in hypertensive patients, 6 may benefit prognosis.…”
Section: Introductionmentioning
confidence: 99%